2007
DOI: 10.1007/s00464-006-0108-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial and total laparoscopic fundoplication on esophageal body motility

Abstract: Laparoscopic fundoplication increased LES pressure and the strength of esophageal peristalsis in patients with abnormal preoperative esophageal motility. A total fundoplication resulted in normalization of peristalsis in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 19 publications
5
39
0
4
Order By: Relevance
“…One year after fundoplication, typical and atypical symptoms were absent in 95-100% of patients, 98% were off proton pump inhibitor (PPI) therapy, manometric characteristics of the lower esophageal sphincter and esophageal acid exposure normalized, and life quality significantly improved [1,2]. Thus, the ''Krems-antireflux program'' seems to be very successful and is in keeping with the results of previously published series [3].…”
Section: Dear Editorsupporting
confidence: 81%
“…One year after fundoplication, typical and atypical symptoms were absent in 95-100% of patients, 98% were off proton pump inhibitor (PPI) therapy, manometric characteristics of the lower esophageal sphincter and esophageal acid exposure normalized, and life quality significantly improved [1,2]. Thus, the ''Krems-antireflux program'' seems to be very successful and is in keeping with the results of previously published series [3].…”
Section: Dear Editorsupporting
confidence: 81%
“…Delayed gastric emptying may play a role in reflux disease, so pyloroplasty is indicated when the delay in gastric emptying is severe. There also is evidence that fundoplication may improve both esophageal and gastric motility [11,17].…”
Section: Systematic Esophageal Preoperative Evaluationmentioning
confidence: 99%
“…Total fundoplication should be the procedure of choice for patients with GERD regardless of the preoperative esophageal motility. In a retrospective study, Herbella et al (10) concluded that total fundoplication more often causes normalization of peristalsis, with consequent amelioration of esophageal clearance. LNF is our operation of choice for GERD.…”
Section: Discussionmentioning
confidence: 99%